Probable Mechanisms of COVID-19 Pathogenesis - R. N. Mustafin; E. K. Khusnutdinova (Креативная хирургия и онкология)
This review paper focuses on the search for innovative directions in the study of COVID19 viral infection with the purpose of improving the methods of its treatment and vaccination. Thus far, comprehensive data have been obtained on the ability of nonretroviral RNA viruses, including those replicated in the cytoplasm, to integrate fragments of their genomes into the host DNA. This mechanism provided by the reverse  transcriptase and integrase of endogenous retroelements leads to the persistence of nonretroviral RNA viruses  through the expression of viral proteins by the host genome, which may serve as a prerequisite for the survival of such viruses. DNA integration events play a role in the development of both the immunological response and protective antiviral responses through the RNA interference system. These mechanisms may depend on the phylogenetically ancient fossils of nonretroviral RNA sequences in animal genomes. The discovery of SARS-CoV-2 fragments in COVID19 recovered patients suggests that the pathogenesis of this disease may be associated with the integration of SARS-CoV-2 genome fragments in the human genome by means of proteins of endogenous retroviral elements. This assumption can be confirmed by the data about the development in older patients of predominantly severe forms of COVID19 with “hyperactive” immune reactions, which normally weaken with ageing. This may be attributed to agerelated abnormal activation of  retrocells, which contribute to reverse transcription and integration of exogenous viruses. This assumption is supported by the presence of coronavirus components in the nuclei of infected cells and the change in the expression of LINE1 in the lung tissue cells of SARS patients. Due to the probable role of retrocells in the COVID19 pathogenesis, LINE1 reverse transcriptase inhibitors and targeted therapy using microRNAs may be offered as promising treatments for COVID19.